2018
DOI: 10.5527/wjn.v7.i6.117
|View full text |Cite
|
Sign up to set email alerts
|

Oral alkali therapy and the management of metabolic acidosis of chronic kidney disease: A narrative literature review

Abstract: Chronic metabolic acidosis is a common complication seen in advanced chronic kidney disease (CKD). There is currently no consensus on its management in the Republic of Ireland. Recent trials have suggested that appropriate active management of metabolic acidosis through oral alkali therapy and modified diet can have a deterring impact on CKD progression. The potential benefits of treatment include preservation of bone health and improvement in muscle function; however, present data is limited. This review high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Around 45,000 premature deaths are attributed to CKD annually in the United Kingdom [3]. Furthermore, the management of CKD places a substantial economic burden on healthcare systems across the globe, and healthcare expenditure has been noted to be inversely proportional to renal function [4]. The National Health Service (NHS) in England spent approximately £1.45 billion on CKD in 2009–2010 [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 45,000 premature deaths are attributed to CKD annually in the United Kingdom [3]. Furthermore, the management of CKD places a substantial economic burden on healthcare systems across the globe, and healthcare expenditure has been noted to be inversely proportional to renal function [4]. The National Health Service (NHS) in England spent approximately £1.45 billion on CKD in 2009–2010 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic acidosis is frequently found in CKD patients, and becomes more common with worsening renal function [4]. Metabolic acidosis has been operationalised as serum bicarbonate levels that are consistently below 22 mmol/L [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buffers are substances that counteract changes in pH [9], and sodium bicarbonate is the most frequently used buffer [30][31]. The main reason to commence sodium bicarbonate therapy is to prevent or reverse the effects of metabolic acidemia, especially in the cardiovascular system [25].…”
Section: Bicarbonate Therapymentioning
confidence: 99%
“…Sodium bicarbonate is a major component of alkali therapy (5), where previous studies have shown that there is an inverse association between sodium bicarbonate administration and acidosis (6,7). Also, sodium bicarbonate therapy has a signi cant increasing effect on serum bicarbonate level (8), thereby conferring a bene cial effect on the bicarbonate buffer system (9).…”
Section: Introductionmentioning
confidence: 99%